IMPLEMENTASI KEARIFAN LOKAL MASYARAKAT SUMATERA BARAT DALAM PELAKSANAAN GADAI TANAH - Adhim, Nur; Triyono, Triyono; Alfriano, Naina (Fakultas Hukum, Universitas Diponegoro, 2019)
ABSTRACT In the Minangkabau community, land is not only for fulfilling living needs, but also related to matrilineal organizations. Talking about land issues in Minanagkabau means talking about Minangkabau customary law as well. Land issues are an integral part of customary law. Thus the close relationship can be seen if the customary law community changes, the law of the land will change, and the law will remain if the community does not change, so that wherever the Minangkabau people are located they are bound by a unity of land law. The implementation of land pawns carried out by the people of West Sumatra has been regulated in such a way by the provisions of customary law. The land pawn has local wisdom that is maintained until now, namely the conditions that must be met before pawning. Submission of pawn money is not done with money but with gold and pawning is carried out based on the principle of social character that functions to help, without extortion or coercion, no one feels aggrieved either the pawning party or the land pawn recipient. Keywords: Land Pawn, People of West Sumatra